Courtyard houses : a housing typology. - Pfeifer, Günter, 1943-; Brauneck, Per, ....- (Basel : Birkhäuser, 2008)
What readers will find in this book is nothing less than a treasure trove of ideas and urban style, particularly useful for architects. To continue developing existing building types in an intelligent way is a crucial task in the field of residential building. For this typology of residential buildings, the authors have developed systematic new presentations of the most innovative types. Each individual volume lays out the possibilities for using and transforming a particular form of residential structure. The first volume deals with the various types of the courtyard house, which utilizes the courtyard as an intimate outdoor living space. A presentation of the courtyard as a building block of the city is followed by coverage of the complete spectrum of types - cluster, network, carpet, terraces, etc. The second volume is devoted to the various types of row house, a particularly widespread form of residential structure. A general discussion of the row as organizing principle - the row as urban building block, linear space, ways of handling corners - is followed by the systematic presentation of the different types.
Keywords: Woningbouw